2016
DOI: 10.1186/s41182-016-0011-z
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized control of human visceral leishmaniasis in endemic urban areas of Brazil: a literature review

Abstract: ObjectivesHuman migration and concomitant HIV infections are likely to bring about major changes in the epidemiology of some parasitic infections in Brazil. Human visceral leishmaniasis (HVL) control is particularly fraught with intricacies. It is against a backdrop of decentralized health care that the complex HVL control initiatives are brought to bear. This comprehensive review aims to explore the obstacles facing decentralized HVL control in urban endemic areas in Brazil.MethodA literature search was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 95 publications
0
25
0
3
Order By: Relevance
“…There have been changes in the epidemiological profile of VL and evidence that both the parasite and the vector have the ability to adapt in different environments (Diro et al , 2014 b ; Castelo Branco et al , 2016). This evidences that there are many obstacles in the control of VL (Menon et al , 2016) and, consequently, HLV/HIV coinfection.…”
Section: Discussionmentioning
confidence: 94%
“…There have been changes in the epidemiological profile of VL and evidence that both the parasite and the vector have the ability to adapt in different environments (Diro et al , 2014 b ; Castelo Branco et al , 2016). This evidences that there are many obstacles in the control of VL (Menon et al , 2016) and, consequently, HLV/HIV coinfection.…”
Section: Discussionmentioning
confidence: 94%
“…Evidence has shown that when a susceptible human, sand-fly or reservoir is infected, there is an incubation period during which the infectious agent develops. The incubation periods for humans, sandflies and reservoir range from 2 to 6 months, 8 to 6 days, and 3 to 7 years, respectively [6,17,18]. Furthermore, to capture the effect of the incubation period on the transmission dynamics of ZVL it is important to incorporate delay caused by the incubation period in the ZVL model.…”
Section: Introductionmentioning
confidence: 99%
“…Na forma clínica mais grave de leishmaniose, a LV, mais de 95% dos casos é fatal se não for tratada, sendo caracterizada por picos febris irregulares, perda de peso, hepatoesplenomegalia e anemia (TORRES-GUERRERO et al, 2017 chagasi (MENON et al, 2016).…”
Section: Leishmanioseunclassified